Ecuador: economics and politics of citizen revolution, preliminary assessment - Arevalo Luna, Guillermo Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article analyses some facts linked to dollarization program carried out in 2000 and its positive effects in macroeconomic stabilization of Ecuador, the reduction in inflation, interest rate and its impact on investment, as well as the economic growth and poverty reduction. We also review fiscal expenditure on social and economic infrastructure as additional variable of economic policy to promote economic growth, employment and general welfare of the population. This paper concludes that dollarization was the key factor to help fiscal policy to obtain economic and social development.